Kesepakatan penilaian Mini Mental State Examination (mmse) pada penderita stroke ikhemik akut di RSUP Dr Sardjito Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Among the brief cognitive batteries that have been used for screening in dementia surveys, the Mini Mental State Examination (MMSE) is one of the most frequently proposed. Evidence is accumulating that stroke is a risk factor associated with cognitive impairment. The association between the MMSE score and level of education is a controvertion. The aim of the study is to determine the reliability of MMSE score in the patients with acute ischaemic stroke in Sardjito General Hospital between two doctors in the neurological ward. As subject is two doctors in the Neurological Ward Sardjito General Hospital who had tried about measured of MMSE score, with the sample are 20 patients of acute ischaemic stroke. Kappa score was used for reliability MMSE score in the patients acute ischaemic stroke between two doctors in the Neurological Ward Sardjito General Hospital with formula which developed by Fleiss. Reliability of MMSE score in the patients of acute ischaemic stroke between two doctors in the Neurological Ward Sardjito General Hospital is the best result with Kappa score is 0,98 ip < 0,00001). Mini Mental State Examination (MMSE) is most reliable for measuring the cognitive impairment and may used by the doctor in the ward.